2017
DOI: 10.1016/j.placenta.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Review: Systematic review of the utility of the fetal cerebroplacental ratio measured at term for the prediction of adverse perinatal outcome

Abstract: The CPR at term has a strong association with adverse obstetric and perinatal outcomes. This review suggests the predictive utility of CPR at term is promising however there is insufficient evidence to demonstrate its value as a stand-alone test. Inclusion of CPR as a component of clinical care may help better identify fetuses at risk of adverse outcome, and this should be tested with randomised control trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 63 publications
3
78
2
6
Order By: Relevance
“…We identified three systematic reviews on the predictive accuracy of CPR for adverse perinatal outcome. Nassr et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified three systematic reviews on the predictive accuracy of CPR for adverse perinatal outcome. Nassr et al .…”
Section: Discussionmentioning
confidence: 99%
“…We identified three systematic reviews on the predictive accuracy of CPR for adverse perinatal outcome [70][71][72] . Nassr et al 70 included seven studies, and reported that abnormal CPR in pregnancies at high risk for FGR or with a diagnosis of FGR increased the risk for adverse perinatal outcome.…”
Section: Interpretation In Light Of Previous Systematic Reviewsmentioning
confidence: 99%
“…Primary outcomes of interest were delivery mode (spontaneous vaginal birth, operative vaginal birth, emergency Cesarean section (CS) and emergency CS for intrapartum fetal distress), intrapartum fetal distress, placental abruption, 5‐min Apgar score < 7, admission to the neonatal intensive care unit (NICU), birth asphyxia, acidosis, periventricular hemorrhage (PVH) and PND. These outcomes were selected as they reflect adverse intrapartum and neonatal outcomes and are consistent with other studies evaluating suboptimal obstetric and perinatal sequelae. Secondary outcomes were PE, LBW (birth weight < 10 th centile) and PTB (birth < 37 weeks' gestation).…”
Section: Methodsmentioning
confidence: 99%
“…The cerebroplacental ratio (CPR) is calculated as the ratio of MCA to UA Doppler, and has been hypothesized to be more accurate than its individual components. An association with adverse perinatal outcome has been the focus of several literature reviews. CPR and MCA Doppler in FGR are gradually becoming integrated into clinical practice and international guidelines, but reported estimates of their accuracy vary considerably.…”
Section: Introductionmentioning
confidence: 99%